The prevalence of mismatch repair deficiency in ovarian cancer: A systematic review and meta‐analysis - Atwal, Amit; Snowsill, Tristan; Dandy, Marcus Cabrera; Krum, Thomas; Newton, Claire; Evans, Dafydd Gareth; Crosbie, Emma J.; Ryan, Neil A. J. (International journal of cancer, 2022)
Ovarian cancer (OC) is the least survivable gynecological malignancy and presents late. Five‐year survival for OC is around 45% increasing the need for innovative treatments. Checkpoint inhibitors have shown significant clinical efficacy in mismatch repair deficient (MMRd) cancers and could be a powerful treatment in OC. However, their application in OC is limited due to the lack of data on the prevalence of MMRd. The aim of our study was to conduct a systematic review of the literature and meta‐analysis to provide an accurate estimate of the prevalence of MMRd in OC. We followed PRISMA guidelines throughout. Studies were identified by electronic searches of Medline, Embase, Cochrane CENTRAL and Web of Science followed by citation searching. Studies not written in English were excluded. All studies were reviewed by at least two independent reviewers. Proportions of test positivity were calculated by random and fixed‐effects meta‐analysis models. I2 score was used to assess heterogeneity across studies. In total 54 studies were included with 17 532 analyzed for MMRd. The overall proportions of MMRd by immunohistochemistry and microsatellite instability analysis were 6.7% and 10.4%, respectively. MMRd was reported in all histotypes of epithelial OC but was most common in endometrioid OC. We estimate that on average 46.7% (95% CI: 28.8‐65.4) of ovarian carcinomas showing MMRd by IHC had a germline path_MMR variant identified. OC in those with Lynch syndrome seems to present at an earlier age and stage. Studies however were generally of low quality and there was a high degree of heterogeneity. A significant minority (up to 16%) of OC displays MMRd and, therefore, could be amenable to checkpoint inhibition therapy. However, the current literature base is of limited quality and therefore high‐quality prospective studies exploring MMRd in OC with the use of multimodal testing are required. In addition, trials researching efficacy of checkpoint inhibition in MMRd OC are needed. What's new? Despite gains in ovarian cancer survival, overall prognosis remains poor. Thus, to further improve patient outcomes', efforts are being made to identify cancers amenable to targeted therapeutics. Ovarian cancers with a mismatch repair deficiency (MMRd) phenotype could respond to immotherapy and therefore defining the prevelance of MMRd in ovarian cancer is important. In the present meta‐analysis examining the prevalence of MMRd in ovarian cancer we found a significant minority of  ovarian cancers are MMRd. MMRd was observed in all histotypes but was more common in endometrioid tumors. Knowledge of MMRd prevalence in ovarian cancer could help guide therapeutic decisions, particularly surrounding the use of checkpoint inhibitors which are most effective in MMRd cancers.